Comparison of micronuclei frequency in bone marrow cells of three rat lines - Arencibia-Arrebola, D.F.; Rosario-Fernandez, L.A.; Suarez-Fernandez, Y.E.; Vidal-Novoa, A. (Цитология и генетика, 2013)
The aim of this paper is to compare the spontaneous and induced with cyclophosphamide micronucleus indexes in bone marrow cells of the Sprague Dawley, Lewis and Wistar rat lines. Five experimental groups were formed (10 animals of each sex and of each line, in every group). The first group was used as the negative control (intact animals), the second one was exposed to oral administration of drugs; other conditions were the same as for the other groups. The third group was treated with 2 % Tween 65 and the fourth group was treated with 0.9 % NaCl. Both substances were administered by oral way to 2 ml/kg during 14 days. The fifth group was treated intraperitoneally with strong mutagen cyclophosphamide in the dose of 50 mg/kg (10 ml/kg in solution), on 48th and 24th hours before euthanasia. The Sprague Dawley line (both sexes) was significantly different from the other lines. Rats of this line had lower index of spontaneous formation of micronuclei, higher index of cyclophosphamideinduced micronucle formation, percent of micronucleated erythrocytes in bone marrow and the index of cytotoxicity. The results obtained make it possible to identify the most appropriate line of rats as model animals for studies of genotoxicity. It will allow also to obtain more accurate estimates of genotoxicity of various substances.